Analisis Semiotika Penggambaran Perempuan Bercadar dalam Film Pendek “Menjadi Aku Tak Harus Kaku” - Muhamad Lutfi Habibi (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, State Islamic University Sunan Kalijaga Yogyakarta, 2021)
The background problem of this research is how the depiction of face-veiled woman is found in the short movie